Suppression of endogenous retroviral enhancers in mouse embryos derived from somatic cell nuclear transfer - Shikata, Daiki; Matoba, Shogo; Hada, Masashi; Sakashita, Akihiko; Inoue, Kimiko; Ogura, Atsuo (Frontiers in Genetics, 2022)
Endogenous retroviruses (ERVs) in the mammalian genome play diverse roles in embryonic development. These developmentally related ERVs are generally repressed in somatic cells and therefore are likely repressed in embryos derived from somatic cell nuclear transfer (SCNT). In this study, we sought to identify ERVs that are repressed in SCNT-derived morulae, which might cause previously unexplained embryonic deaths shortly after implantation. Our transcriptome analysis revealed that, amongst ERV families, ERVK was specifically and strongly downregulated in SCNT-derived embryos while other transposable elements including LINE and ERVL were unchanged. Among the subfamilies of ERVK, RLTR45-int was most repressed in SCNT-derived embryos despite its highest expression in control fertilized embryos. Interestingly, the nearby genes (within 5–50 kb, n = 18; 50–200 kb, n = 63) of the repressed RLTR45-int loci were also repressed in SCNT-derived embryos, with a significant correlation between them. Furthermore, lysine H3K27 acetylation was enriched around the RLTR45-int loci. These findings indicate that RLTR45-int elements function as enhancers of nearby genes. Indeed, deletion of two sequential RLTR45-int loci on chromosome 4 or 18 resulted in downregulations of nearby genes at the morula stage. We also found that RLTR45-int loci, especially SCNT-low, enhancer-like loci, were strongly enriched with H3K9me3, a repressive histone mark. Importantly, these H3K9me3-enriched regions were not activated by overexpression of H3K9me3 demethylase Kdm4d in SCNT-derived embryos, suggesting the presence of another epigenetic barrier repressing their expressions and enhancer activities in SCNT embryos. Thus, we identified ERVK subfamily RLTR45-int, putative enhancer elements, as a strong reprogramming barrier for SCNT.